Electrochemical biosensor for simultaneously detection of Tamoxifen - Hasret Subak (MANAS: Journal of Engineering)
Cancer is described as the uncontrollably multiplying abnormal proliferation of cells. Cancer can affect everyone, and risk of which rises with age, lifestyle, and environmental toxins. Tamoxi̇fen (TAM) which is a selective estrogen receptor modulator, has estrogenic or antiestrogenic effects on the breast tissue by binding to the estrogen receptors. The current study presents a voltammetric biosensor to identify the effect of Tamoxifen on DNA structure. In this study, the effect of TAM on the double-stranded DNA (dsDNA) was investigated electrochemically in both the presence and absence of antioxidants. For this purpose, TAM-dsDNA-antioxidant interaction investigated by using the pencil graphite electrode (PGE). The DNA modified sensor was created simply by wet-adsorbtion method. The prepared biosensor was examined electrochemically by square wave voltammety (SWV) method, and its lowest concentration and optimum pH range were determined. The effect of TAM on dsDNA was investigated simultaneously for the first time in the literature.